Lactate-to-Albumin Ratio (LAR) as a Predictor of All-Cause Mortality in Patients With Myocardial Infarction: A Systematic Review and Meta-Analysis - Ul Islam, Mujahed; Gollapinni, Uday; Ul Hassan, Shabab; Saleem, Muhammad Mohsin; Venkannagari, Harshith R; Chaudhari, Sandipkumar S; Mohsin, Moaz; Khan, Areeba (Curēus (Palo Alto, CA), 2025)
Myocardial infarction (MI) remains a significant global health challenge, necessitating innovative approaches for early risk stratification. This systematic review and meta-analysis investigated the prognostic value of the lactate-to-albumin ratio (LAR) in predicting all-cause mortality among MI patients. A comprehensive literature search was conducted across PubMed, Embase, Web of Science, and Google Scholar, encompassing studies published until March 10, 2025. The meta-analysis included five studies involving 8,408 subjects with MI, all conducted in China between 2022 and 2024. Studies were selected based on predefined eligibility criteria, focusing on observational cohort and case-control designs, with LAR measured at admission and mortality outcomes reported. Pooled analysis revealed that patients with high LAR experienced approximately twice the risk of all-cause mortality compared to those with low LAR (hazard ratio: 2.08, 95% confidence interval: 1.70-2.54,p < 0.001). Significant heterogeneity was observed among studies (I : 75%), which may be attributed to variations in patient populations and measurement methodologies. Despite limitations such as retrospective study designs and potential selection bias, the findings suggest LAR as a promising, accessible biomarker for early risk stratification in MI patients. Future research should focus on prospective studies to validate these results, establish standardized measurement protocols, and explore the underlying physiological mechanisms linking LAR to adverse outcomes.